Fresno County Young Lawyers Association Hopper Luncheon with California Supreme Court Justice John Racanelli - Watkins, Howard::::::::: (1986)
Fresno County Young Lawyers Association President Brad Geery, Justice Hollis Best introducing keynote speaker, Justice John Racanelli and Betty Racanelli